Social role performance and self-identity among breast cancer patients in Lagos, Nigeria - Samuel Ojima Adejoh; Deborah Tolulope Esan; Adeola Adejayan (Journal of Health and Social Sciences)
Introduction: Aim of this study was to explore the impact of breast cancer diagnosis and treatment on perceived self-identity and family, social and occupational roles perfomance of women in Nigeria. Methods: A qualitative method was adopted by face-to-face, semi-structured interviews administered to a sample of 15 women. The population study comprised of women who were diagnosed with breast cancer, had undergone surgery, and were currently or recently receiving chemotherapy and/or radiotherapy at private hospitals in Ikeja, capital of Lagos State, Nigeria, from December 2015 to March 2016. Results and Discussion: A total of 15 women with breast cancer, between 30 and 60 years of age (M = 42.3), participated in this study. All the respondents were married, had children and were working before the cancer diagnosis. Our findings showed that breast cancer diagnosis and treatment may alter role performance of women in their families, workplaces and community in which they live, and may affect negatively their self-identity, due to negative self-image and self-perception, and due to fear to be socially stigmatised by neighbours. However, women with such diagnosis may find support within their religious circles, as spirituality might be an important coping mechanism for this patient popolution. Conclusion: In Nigeria, policy makers should support women diagnosed with breast cancer through economic investments to set up socio-occupational support networks at national and local levels.